Is there any relationship between the time spent in respiratory events and cardiovascular morbidity in obstructive sleep apnea patients? - Yilmaz Durmaz, Dilber; Gunes, Aygul; Yildiz, Tekin (Annals of Medical Research, 2021)
Aim: The importance of the duration of respiratory events, in addition to the number, in the evaluation of obstructive sleep apnea (OSA) is gradually increasing. We aimed to investigate whether parameter including the number and duration of respiratory events predict cardiovascular mortality. Material and Methods: A retrospective study included 200 patients with OSA (100 severe, 50 moderate, 50 mild). Time spent during respiratory events, including the number and duration of respiratory events, was calculated for each respiratory event. Obstructive apnea time (OAT), hypopnea time (HT), total apnea time (TAT), and total respiratory event time (TRET) were obtained. The relationship between cardiovascular diseases of the patients and the time spent during respiratory events was examined. Results: There was no relationship between the cardiovascular diseases and the time spent during respiratory events in the mild, moderate and all OSA group; however, the prolonged OAT (p=0.024) and TAT (p=0.039) in the severe OSA group were associated with an increase in the cardiovascular diseases, independent of other variables. However, the relationship between apnea-hypopnea index (AHI) and cardiovascular diseases in mild, moderate, severe, and all OSA was not significant.Conclusion: Using parameters including the duration of respiratory events in addition to AHI may be more useful to understand the comorbidities of OSA particularly cardiovascular diseases.
Keywords: Cardiovascular disease; duration; obstructive sleep apnea; respiratory event